Ultrasonography of the Peripheral Nerves of the Forearm, Wrist and Hand: Definition of Landmarks, Anatomical Correlation and Clinical Implications - Gruber, Leonhard; Loizides, Alexander; Peer, Siegfried; Walchhofer, Lisa Maria; Spiss, Verena; Brenner, Erich; Stahl, Kathrin; Gruber, Hannes (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background Peripheral nerve pathologies of the upper extremity are increasingly assessed by high-resolution ultrasonography (HRUS), yet rapid identification of nerve segments can be difficult due to small nerve diameters and complex regional anatomy. We propose a landmark-based approach to speed up and facilitate evaluation and intervention in this region.Method Relevant landmarks and section planes for eleven nerve segments of the forearm, wrist and hand were defined by ultrasonography in cadaver arms before cryosection and topographical neurovascular preparation. Information on all nerve segments and a pictorial guide including anatomical cross-sections, topographical preparations and HRUS images are provided. The identification rates of these nerve segments were then assessed in 20 healthy volunteers.Results and Conclusion Sonographic landmarks and guidelines for the rapid identification and assessment of nerves of the forearm, wrist and hand are presented in pictorial and tabular form, including discussion of normal variants. Utilizing this overview should facilitate training, diagnostic examinations and intervention for nerves of the upper extremity.Key Points: Citation Format
Keywords: ultrasound; anatomy; nervous-peripheral; hand